2019
DOI: 10.1038/s41419-019-1698-7
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA SNHG1 promotes glioma progression by competitively binding to miR-194 to regulate PHLDA1 expression

Abstract: Long non-coding RNAs (lncRNAs) play a vital role in tumourigenesis, including that of glioma. Small nucleolar RNA host gene 1 (SNHG1) is a relatively novel lncRNA that is involved in the development of multiple human tumours. However, its underlying molecular mechanism in glioma has not been completely clarified. In this study, we show that SNHG1 is overexpressed in glioma tissues and cell lines. A series of functional assays suggested that SNHG1 promotes glioma progression in vitro and in vivo. Next, through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 36 publications
(37 reference statements)
1
53
0
Order By: Relevance
“…[13][14][15] Decreased expression of miR-194-5p has been reported in various types of malignancy, including glioma, hepatoma carcinoma, gallbladder carcinoma and acute myeloid leukaemia. [16][17][18][19] Overexpressed miR-194-5p in non-small-cell lung cancer suppresses cell migration, invasion and metastasis. 20 These reports indicate that miR-194-5p functions as a tumour suppressor in various human malignancies.…”
mentioning
confidence: 99%
“…[13][14][15] Decreased expression of miR-194-5p has been reported in various types of malignancy, including glioma, hepatoma carcinoma, gallbladder carcinoma and acute myeloid leukaemia. [16][17][18][19] Overexpressed miR-194-5p in non-small-cell lung cancer suppresses cell migration, invasion and metastasis. 20 These reports indicate that miR-194-5p functions as a tumour suppressor in various human malignancies.…”
mentioning
confidence: 99%
“…LncRNAs showed essential roles in glioma progression. [87][88][89] It was found that LINC00909 has a role as a ceRNA by interacting with miR-194 and finally upregulates MUC1-C leading to promote the proliferation and the invasion of glioma cells. Accordingly, LINC00909 upregulation is linked to advanced World Health Organization (WHO) grade, and also poor prognosis in glioma patients.…”
Section: Gliomamentioning
confidence: 99%
“…87 signaling pathway may be a potential therapeutic strategy for glioma patients. 88 In an experimental study, it was observed that suppressing cyclooxygenase-2 (COX-2), microsomal prostaglandin E synthase-1 (mPGES-1), and cytochrome P450 4A11 (CYP4A) in the C6 and U87 glioma cells by flavonoid isoliquiritigenin, inhibited the Akt-FGF-2/TGFβ/VEGF angiogenic signaling pathway through ceRNA effect of lncRNA NEAT1 and miR-194 and could be introduced as a new therapeutic approach for glioma patients. 89 miR-215 was first discovered as a regulator of p53.…”
Section: Gliomamentioning
confidence: 99%
“…Elevated serum levels of miR-194-5p have been associated with cancers of peripheral organs such as the kidneys and liver [104,105]. Interestingly, elevated miR-194-5p in the serum is also associated with promotion of glioma development as well as generalized epilepsy [106,107]. Both miR-22-3p and miR-152-3p have been shown to be differentially expressed in plasma-derived EV miRNA from AD patients [108].…”
Section: Methamphetaminementioning
confidence: 99%